Alright! Let's break it down in a way that a 6th grader would understand:
We start with the equation:
\[ 32 = -25 + 9 - x + x + 7 \]
First, we need to simplify the right side. We can combine the numbers together!
- Adding these together: \(-25 + 9 + 7\) gives us \(-25 + 9 = -16\) and then \(-16 + 7 = -9\).
So now our equation looks like this:
\[ 32 = -9 \]
Now, we can turn this into two separate statements. One way to do it is to say:
-
The first equation, taking away \(x\) since it cancels out in this case, is: \(-25 + 9 = -9\)
-
The second equation is: \(32 = -9\) (but that's not true).
Instead, let's choose something that makes more sense. We can use:
- \(32 = 32\) (which is true!)
- \(-9 = -9\) (which is also true!)
So, we can say:
Answer: \[ 32 = 32 \text{ and } -9 = -9 \]
Both of these statements are true, and they connect nicely!